2002
DOI: 10.1046/j.1460-9568.2002.02150.x
|View full text |Cite
|
Sign up to set email alerts
|

5‐HT4 receptors exert a frequency‐related facilitatory control on dorsal raphé nucleus 5‐HT neuronal activity

Abstract: We investigated, using single-unit recordings in chloral hydrate-anaesthetized rats, the role of serotonin 4 (5-HT4) receptors in the control of dorsal raphé nucleus (DRN) 5-HT neuron activity. About one-half (36) of the 76 neurons recorded were affected by either the preferential 5-HT4 agonist cisapride (500 and 1000 micro g/kg, i.v.) or the selective 5-HT4 antagonist, GR 125487 (200- 2000 micro g/kg, i.v.). Responding neurons displayed a significantly higher mean basal firing rate (1.93 +/- 0.1 Hz) than non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 28 publications
(48 reference statements)
7
48
0
Order By: Relevance
“…The fast onset of action of the 5-HT 4 receptor agonist could be a consequence of an increase in serotonergic output to projection areas (Lucas et al, 2005;Lucas and Debonnel, 2002). Indeed, by measuring spontaneous electrical activity in mice lacking 5-HT 4 receptors, Conductier et al (2006) demonstrated that 5-HT 4 receptors exert a tonic positive influence on the firing activity of dorsal raphe nucleus 5-HT neurons, and previous studies have shown that 5-HT 4 receptor activation by selective agonists modulates central 5-HT neurotransmission, increasing the firing of dorsal raphe nucleus 5-HT neurons (Lucas and Debonnel, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fast onset of action of the 5-HT 4 receptor agonist could be a consequence of an increase in serotonergic output to projection areas (Lucas et al, 2005;Lucas and Debonnel, 2002). Indeed, by measuring spontaneous electrical activity in mice lacking 5-HT 4 receptors, Conductier et al (2006) demonstrated that 5-HT 4 receptors exert a tonic positive influence on the firing activity of dorsal raphe nucleus 5-HT neurons, and previous studies have shown that 5-HT 4 receptor activation by selective agonists modulates central 5-HT neurotransmission, increasing the firing of dorsal raphe nucleus 5-HT neurons (Lucas and Debonnel, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, by measuring spontaneous electrical activity in mice lacking 5-HT 4 receptors, Conductier et al (2006) demonstrated that 5-HT 4 receptors exert a tonic positive influence on the firing activity of dorsal raphe nucleus 5-HT neurons, and previous studies have shown that 5-HT 4 receptor activation by selective agonists modulates central 5-HT neurotransmission, increasing the firing of dorsal raphe nucleus 5-HT neurons (Lucas and Debonnel, 2002). There is also accumulating evidence that cortical regions are involved in 5-HT4-induced anxiolytic/antidepressant-like activities (Lucas et al, 2005) (for review see also (Lucas, 2009)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both 5-HT4-Rs and 5-HT5A-Rs have been shown to exert negative feedback control over the DRN, probably via an indirect, mPFC-mediated, and a direct, autoreceptor-mediated, mechanism respectively (Lucas et al, 2005;Lucas and Debonnel, 2002;Thomas et al, 2006). Genetic deletion of the mouse Htr5a has minimal effect on anxiety-like behavior .…”
Section: -Ht4 5-ht5a 5-ht6 and 5-ht7 Receptorsmentioning
confidence: 99%
“…Interestingly, 5-HT 4 Rs exert both a tonic and a phasic stimulatory control over dorsal 5-HT raphe neurons (Lucas and Debonnel 2002). This effect might be enhanced by the activation of 5-HT 4 Rs expressed in the medial prefrontal cortex (Lucas et al 2005).…”
Section: -Ht 4 Rsmentioning
confidence: 99%